Regioselective Iodine/Zinc Exchange for the Selective Functionalization of Polyiodinated Arenes and Heterocycles in Toluene - Sanchez, Florian; Desaintjean, Alexandre; Danton, Fanny; Knochel, Paul (Synthesis, 2021)
Regioselective I/Zn-exchange reactions were performed on polyiodinated arenes or heterocycles within 20 minutes at 0–25 °C using the bimetallic combination pTol2Zn·2LiOR [R = (CH2)2N(Me)(CH2)2NMe2] in toluene. The resulting diaryl- or diheteroarylzincs reacted well with allylic bromides and acyl chlorides to provide functionalized (hetero)aryl iodides in good yields.
Keywords: alkoxides; apolar solvents; arenes; heterocycles; lithium; regioselective iodine/zinc exchange; zinc